Microalgae in aquafeeds for a sustainable aquaculture industry - Shah, Mahfuzur Rahman; Lutzu, Giovanni Antonio; Alam, Asraful; Sarker, Pallab; Kabir Chowdhury, M. A.; Parsaeimehr, Ali; Liang, Yuanmei; Daroch, Maurycy (Journal of applied phycology, 2018)
Due to the rapid global expansion of the aquaculture industry, access to key feedstuffs (fishmeal and fish oil) is becoming increasingly limited because of the finite resources available for wild fish harvesting. This has resulted in other sources of feedstuffs being investigated, namely plant origin substitutes for fishmeal and fish oil for aquafeed. Conventional land-based crops have been favored for some applications as substitutes for a portion of the fishmeal, but they can result in changes in the nutritional quality of the fish produced. Microalgae can be regarded as a promising alternative that can replace fishmeal and fish oil and ensure sustainability standards in aquaculture. They have a potential for use in aquaculture as they are sources of protein, lipid, vitamins, minerals, pigments, etc. This comprehensive review summarizes the most important and recent developments of microalgae use as supplement or feed additive to replace fishmeal and fish oil for use in aquaculture. It also reflects the microalgal nutritional quality and digestibility of microalgae-based aquafeed. Simultaneously, safety and regulatory aspects of microalgae feed applications, major challenges on the use microalgae in aquafeed in commercial production, and future research and development perspective are also presented in a critical manner. This review will serve as a useful guide to present current status of knowledge and highlight key areas for future development of a microalgae-based aquafeed industry and overall development of a sustainable aquaculture industry.